Retinal neurogenesis - Centanin, Lázaro; Wittbrodt, Joachim (Development, 2014)
A unique feature of humans is the complexity of our central nervous system. A fully functional brain requires that billions of neurons make specific contacts in a highly coordinated way, an issue that is still not well understood. The neural retina constitutes an excellent system with which to analyze key aspects of neurogenesis and circuit formation in the central nervous system. Here, we provide an overview of retinal neurogenesis in vertebrates and discuss implications of the developmental mechanisms involved for regenerative therapy approaches.